Priorities for enhancing the ex situ conservation and use of Australian crop wild relatives - Norton, Sally L.; Khoury, Colin K.; Sosa, Chrystian C.; Castañeda Álvarez, Nora P.; Achicanoy Estrella, Harold Armando; Sotelo, Steven (Commonwealth Scientific and Industrial Research Organisation, 2017)
Crop wild relatives – the wild cousins of cultivated plants – are increasingly recognised for their potential to contribute to the productivity, nutritional quality and sustainability of agricultural crops. However, the use of these genetic resources is dependent upon their conservation in genebanks and consequent availability to plant breeders, the status of which has not been comprehensively analysed in Australia. Such conservation assessments are given urgency by reports of increasing threats to natural populations due to habitat destruction, climate change, and invasive species, among other causes. Here we document Australian wild plants related to important food crops, and outline their priorities for ex situ conservation. Given that no major domesticated food plants originated in the country, Australia’s native flora of crop wild relatives is surprisingly rich, including potentially valuable cousins of banana, eggplant, melon, mung bean, pigeonpea, rice, sorghum, sweetpotato, soybean and yam. Species richness of the wild relatives of major food crops is concentrated in the northern and north-eastern tropical regions, in the Northern Territory, Western Australia, and Queensland. Geographic priorities for collecting of these taxa for ex situ conservation, due to the limited representation of their populations in genebanks, largely align with areas of high species richness. Proposed dam building and agricultural expansion in northern Australia make conservation action for these species more urgent. We outline key steps needed for enhancing the ex situ conservation of Australia’s heritage of major food crop wild relatives, and discuss the critical activities required to increase their use.